Acute Transverse Myelitis as an Uncommon Presentation of Neurobrucellosis: A Case Report - Saja Karaja; Waddah Kazkz (Clinical Case Reports)
ABSTRACT Brucellosis mainly affects the musculoskeletal system with neurological manifestations observed in < 5% of all cases. This report outlines a unique case of neurobrucellosis that resulted in acute transverse myelitis (TM) with absent deep reflexes and negative Wright's reaction. In endemic regions, neurobrocellosis should be considered as a potential etiology of acute TM. Timely initiation of treatment is essential for optimizing clinical outcomes.